Marguerite Duras : apocalyptic desires - Hill, Leslie, 1949- (Routledge, 1993)
The first fully detailed, complete account in English of the fiction and films of France's best-known and most controversial woman writer. Leslie Hill throws new light on Duras' relation with feminism, sexuality and psychoanalysis.